Shifting on Usik Liau game in Wara ceremony towards Hindu Kaharingan society of Dayak Dusun - Derson, -; Subagiasta, I Ketut; Dharmika, Ida Bagus (International Research Journal of Management, IT & Social Sciences (IRJMIS), 2018)
The Hindu Kaharingan society of Dayak Dusun in South Barito watershed has a very strong divine insight as reflected in the aspects of their lives. The religion was not in the major religions, Islam, Christianity, Catholicism, Buddhism, and Hinduism. It was not limited to the world of its tribal environment. It was related to the essential for its own ancestors. Hindu doctrine that was often seen generally regarding the implementation of the religious ceremonies. It was called yadnya. It defined as the sacred sacrifices were conducted sincerely. Due to the diversity for each activity, it was done in accordance with the concept included Desa (place), Kala (time), and Patra (situation and condition). Kaharingan Hindu society was located in the South Barito watershed. There was a mandatory ceremony to be performed. The Liau ancestors can be detached from suffering and misery and could reach the realm of eternity. It was Lummut mountain. Usik Liaugame still exists in the Hindu Kaharingan society although it was often classified that the game as a deviant behavior. Due to it was toward the values of Hinduism and positive law. The religious meaning values of the game were forwarded to the ancestors. The now game implementation ceremony has undergone a shift. The society was bound to the tradition. It was assumed that the game was a pure traditional ceremony was inserted with a gambling game made the event to do business for the momentary benefit. The ritual ceremony was mandatory to be implemented as a form of devotion to his ancestral devotion.